Synthesis, Characterization, Electrochemical and Electropolymerization Properties of Novel Phthalocyanines Functionalized with 4-(2-methoxy-5-(((4-morpholinophenyl)imino)methyl)phenoxy) Units - Akyuz, Duygu; Demirbas, Umit; Tasyurek, Hayat; Kantekin, Halit (Elsevier Science Sa, 2025)
Novel metallophthalocyanines (6-8) bearing 4-(2-methoxy-5-(((4-morpholinophenyl)imino)methyl)phenoxy) substituents were synthesized and thoroughly characterized. The structures of the key intermediates and final phthalocyanine complexes were confirmed by FT-IR, 1H NMR, and mass spectrometry. The electrochemical properties of the newly synthesized nickel(II) (6), cobalt(II) (7), and copper(II) (8) phthalocyanines were investigated using cyclic voltammetry (CV) and square wave voltammetry (SWV). Among them, the cobalt(II) phthalocyanine (7) exhibited a distinct metal-centered redox process due to the redox-active nature of its central metal ion, while the nickel(II) (6) and copper(II) (8) analogs displayed relatively limited electrochemical activity. All three complexes showed nearly reversible redox behavior, as evidenced by scan rate-dependent peak current changes. Electropolymerization studies revealed that increasing polymer film thickness led to reduced conductivity and diminished peak currents, accompanied by shifts in oxidation potentials. These findings underscore the significant role of the central metal ion and polymer film characteristics in modulating electrochemical performance. The synthesized phthalocyanines (6-8) also demonstrated promising potential for modifying electrode surfaces, offering improved electrical conductivity, enhanced stability, corrosion resistance, and suitability for sensor and protective coating applications.
Keywords: Electrochemistry; Electropolymerization; Metallo phthalocyanines; Schiff bases; Morpholines